Engineering of Lurasidone Hydrochloride Loaded Niosomes for Enhancing the Antipsychotic Potential for Nasal Administration - Sharma, Sumit; Sharma, Jai B.; Kumar, Manish; Verma, Ravinder; Kaushik, Deepak; Bhatt, Shailendra (Current Nanomedicine, 2023)
Background: Drugs having high first-pass metabolism or that are susceptible to enzymatic degradation can be administered through the nasal route to avoid their degradation. Lurasidone exhibits less toxicity and side effects as compared to its sister drugs like risperidone, ziprasidone, clozapine, etc. Objective: The present study aimed to develop Lurasidone loaded niosomes for nasal delivery. Methods: Lurasidone niosomes were developed by adapting the ether injection method and optimized using a central composite design. In vitro and in vivo studies were conducted using optimized formulation. Results: The findings showed that the optimized formulation exhibited a particle size of 159.02 ± 0.58 nm and an entrapment efficiency of 91.6 ± 1.6%. The findings from the nasal histopathological analysis revealed that the optimized formulation was non-irritant and non-toxic for nasal mucosa. The findings from in vitro studies revealed 94.61 ± 0.27% of drug release from optimized formulation F7 throughout 24 hrs. The findings of in vivo (Albino Wistar rats) studies demonstrated that various pharmacokinetic parameters (Cmax, Tmax, AUC(0-24), T1/2, Vd and Cl) and pharmcodynamic parameters (conditioned avoidance response, biochemical estimation using oxidative markers such as superoxide dismutase, malondialdehyde and glutathione) were significantly improved compared to marketed tablets (Lurasid® 40 mg) and pure drug suspension. Optimized formulation F-7 exhibited 4.9 times more bioavailability than that of pure drug suspension following intranasal administration. Conclusion: These findings indicate that nasal niosomal formulation of Lurasidone HCl is a promising nanoplatform for enhancing the overall performance of Lurasidone. These results could open new avenues into the future of nanomedicine.
Keywords: conditioned avoidance response